KELOMPOK USAHA OLAHAN TEPUNG JAGUNG DI KABUPATEN BLORA PROVINSI JAWA TENGAH - Arief, Ulfah Mediaty; Setyaningsih, Dyah Nurani (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
The agricultural production in Desa Sambong Ledok District of Blora besides rice are also in the form of corn. The world of industry (SMEs) in the village Ledok Sambong Dis- trict of Blora using corn as an ingredient processed into corn flour. Drying corn flour pro- cessed from corn starch by relying on sunlight. By the time the rain drying process encountered resistance  so  that  the  production  decline.  Science  and  technology  program  for  the  Commu- nity (IbM) providing solutions to design and make a dryer for processed corn into cornmeal on SMEs Egg Roll Corn “Patra Sutra” brand and SMEs Corn Crackers “Maju Sejahtera” brand at Desa Sambong Ledok District of Blora. Drying tool is made with a capacity of 20-30 kg of maize  flour can  dry  within  a  day,  this  drying  appliance  can  use  electricity  or  gas  source. The results obtained in this IbM activity is the production can run smoothly and increase product quality corn flour are homogeneous, hyegienic and durable, as well as the drying process which is more efficient